2020
DOI: 10.1002/uog.21997
|View full text |Cite
|
Sign up to set email alerts
|

Safety of non‐steroidal anti‐inflammatory drugs in postpartum period in women with hypertensive disorders of pregnancy: systematic review and meta‐analysis

Abstract: Objective To assess the effect of non‐steroidal anti‐inflammatory drugs (NSAIDs) on blood pressure when administered for postpartum analgesia in women with hypertensive disorders of pregnancy. Methods MEDLINE, Scopus, CENTRAL, http://Clinicaltrials.gov and Google Scholar databases were searched systematically from inception to 5 December 2019 for studies evaluating the safety of postpartum NSAIDs in women with any gestational hypertensive disorder. Randomized controlled trials (RCTs) and cohort studies were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…[133][134][135] A recent systematic review and meta-analysis that included 5 randomized controlled trials and 5 retrospective cohorts concluded that compared with acetaminophen, nonsteroidal antiinflammatory drugs were not associated with increased BPs up to discharge (2-4 days postpartum). 136 The authors considered the quality of evidence to be low because of the small sample sizes, imprecise results, and short duration of follow-up. Additional investigation is needed to address the impact of longer duration of postpartum nonsteroidal anti-inflammatory drug use in older women with chronic hypertension and additional renal and cardiovascular risk factors.…”
Section: Postpartum Hypertension and Postpartum Preeclampsiamentioning
confidence: 99%
“…[133][134][135] A recent systematic review and meta-analysis that included 5 randomized controlled trials and 5 retrospective cohorts concluded that compared with acetaminophen, nonsteroidal antiinflammatory drugs were not associated with increased BPs up to discharge (2-4 days postpartum). 136 The authors considered the quality of evidence to be low because of the small sample sizes, imprecise results, and short duration of follow-up. Additional investigation is needed to address the impact of longer duration of postpartum nonsteroidal anti-inflammatory drug use in older women with chronic hypertension and additional renal and cardiovascular risk factors.…”
Section: Postpartum Hypertension and Postpartum Preeclampsiamentioning
confidence: 99%
“…Published between 2000 and 2020, the SRs included a total of 740 studies (not accounting for some overlap across SRs), with a median of 15 studies per SR (interquartile range 10–37). All 26 SRs assessed pharmacologic interventions: eight assessed NSAIDs, 38–45 two antiepileptics, 46–48 two β‐blockers, 49–51 two calcium channel blockers, 50,52 two antiemetics (5‐HT3 receptor antagonists), 53,54 two antipsychotics, 55,56 two antihistamines, 57,58 and one each assessed serotonin and norepinephrine reuptake inhibitors (SNRIs), 59,60 tricyclic antidepressants, 59,60 benzodiazepines, 61,62 corticosteroids, 63 oral magnesium, 64 triptans (5‐HT1B/1D receptor agonists), 65 analgesics/antipyretics, 66 and intravenous magnesium 67 . Twelve SRs reported maternal adverse effects and 23 reported fetal/child adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…NSAIDs, [38][39][40][41][42][43][44][45] two antiepileptics, [46][47][48] two β-blockers, [49][50][51] two calcium channel blockers, 50,52 two antiemetics (5-HT3 receptor antagonists), 53,54 two antipsychotics, 55,56 two antihistamines, 57,58 and one each assessed serotonin and norepinephrine reuptake inhibitors (SNRIs), 59,60 tricyclic antidepressants, 59,60 benzodiazepines, 61,62 corticosteroids, 63 oral magnesium, 64 triptans (5-HT1B/1D receptor agonists), 65 analgesics/antipyretics, 66 and intravenous magnesium. 67 Twelve SRs reported maternal adverse effects and 23 reported fetal/child adverse effects.…”
Section: All 26 Srs Assessed Pharmacologic Interventions: Eight Assessedmentioning
confidence: 99%
“…The characteristics of these SRs are summarized in Table 2 , Table 3 and Table 4 . Furthermore, from the 8 SRs including both RCTs and NRSs, 4 SRs [ 103 , 105 , 108 , 109 ] rated the certainty of evidence derived from RCTs and NRSs separately (in separate rows within a single Summary of Findings table, or in separate Summary of Findings tables), 2 SR [ 102 , 104 ] pooled RCTs and NRSs rated the combined evidence (in the same rows within a single Summary of Findings table), 2 SRs [ 106 , 107 ] rated only evidence from NRSs.…”
Section: Resultsmentioning
confidence: 99%